2016
DOI: 10.1007/s10047-016-0892-y
|View full text |Cite
|
Sign up to set email alerts
|

Safe ECMO femoral decannulation by placement of inferior vena cava filter via internal jugular vein

Abstract: Veno-arterial extracorporeal membrane oxygenation (ECMO) is a lifesaving treatment in patients with cardiogenic shock or cardiac arrest caused by massive pulmonary embolism. In these patients, positioning an inferior vena cava filter is often advisable, especially if deep venous thrombosis is not resolved at the time of the ECMO suspension. Moreover, in ECMO patients, a high incidence of deep venous thrombosis at the site of venous cannulation has been reported, and massive pulmonary embolism following ECMO de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…DVT has been reported to affect up to 18% of patients on venovenous ECMO, 5 although this number is likely underestimated and could result in death. [1][2][3] Additionally, authors have reported an increased risk of VTE in patients with ARDS owing to influenza A H1N1, which may be seen in other etiologies resulting in ARDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DVT has been reported to affect up to 18% of patients on venovenous ECMO, 5 although this number is likely underestimated and could result in death. [1][2][3] Additionally, authors have reported an increased risk of VTE in patients with ARDS owing to influenza A H1N1, which may be seen in other etiologies resulting in ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…Given the frequent presence of deep vein thrombosis (DVT) in patients undergoing extracorporeal membranous oxygenation (ECMO), [1][2][3][4][5] inferior vena cava (IVC) filter placement can be performed in tandem with ECMO decannulation to avoid the potentially lethal complication of pulmonary embolism. 4,5 However, the presence of a fibrin sheath in the cava may complicate filter placement, leading to inadequate expansion of the filter struts and insufficient caval filtration. 6 This report describes the bedside use of a balloon catheter under intravascular ultrasound (IVUS) guidance to disrupt an ECMO cannularelated fibrin sheath and facilitate IVC filter placement.…”
mentioning
confidence: 99%
“…Deep venous thrombosis is a known complication of ECMO due to prolonged periods of in situ cannulas, and there is a high risk of massive pulmonary embolism during decannulation. 9 Placement of an IVC filter prior to decannulation can prevent this complication.…”
Section: Case Descriptionmentioning
confidence: 99%
“…Rare yet deadly types of VTE including inferior vena cava (IVC) and superior vena cava (SVC) thrombosis and even SVC syndrome in the setting of ECMO have also been reported in some case reports [21,30,31]. Risk of VTE is not only during the period of ECMO use, it is also seen after decannulation [32].…”
Section: Ecmo Usage and Subsequent Vtementioning
confidence: 99%
“…Moreover, recognizing risk factors may be beneficial in identifying high risk population, ensuring close monitoring, and having a low threshold to consider VTE in the differential diagnosis for these patients. Studies have also experimented with IVC filter placement during decannulation to prevent subsequent VTE in patients [75]. Seeing as many patients suffer thrombotic complications upon decannulation, this method could be useful in conjunction with other preventative measures.…”
Section: Early Identification Prevention and Management Of Vtementioning
confidence: 99%